GAYA BAHASA SARKASME KOMENTAR INSTAGRAMPEMBERHENTIAN TIDAK DENGAN HORMAT (PTDH)FUNGSIONARIS BEM UNIVERSITAS UDAYANA 2023 - Malsa Mega Lestari; I Nyoman Suparwa; Ida Bagus Gede Dharma Putra (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study aims to analyze the types of sarcasm and the violations of politeness maxims found in Instagram comments on the post regarding the Dishonorable Discharge (PTDH) of the Student Executive Board (BEM) functionaries of Udayana University in 2023. This research employs a descriptive qualitative approach using the sarcasm theory proposed by Marta Dynel (2014) and the politeness principle introduced by Geoffrey Leech (1983). The data source consists of netizens’ comments on the Instagram post uploaded by the official account @bem_udayana concerning the PTDH case of BEM Udayana University functionaries on August 21, 2023. The data analyzed comprise 67 comments containing sarcastic expressions. Data collection was conducted through observation and note-taking techniques, while the data were analyzed using the pragmatic identity method. The findings reveal four types of sarcasm, namely mock politeness, covert sarcasm, blatant sarcasm, and covert sarcasm. Among these, blatant sarcasm was identified as the most dominant type, as most comments conveyed criticism and mockery in a direct and explicit manner. Furthermore, the study found violations of the six politeness maxims proposed by Leech, including the tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. Violations of the approbation and sympathy maxims were the most dominant forms, as many comments contained insults, sarcastic remarks, and a lack of empathy toward the individuals involved in the case. The study demonstrates that social media functions as a public space that enables the emergence of various forms of sarcasm as a means of expressing social criticism.